[PS 01-13] RELATIONSHIP OF EMOTIONAL INTELLIGENCE WITH PRE HYPERTENSION AND ITS IMPACT ON AUTONOMIC NERVOUS SYSTEM AS ASSESSED BY HEART RATE VARIABILITY IN ADULT MALES. (September 2016) - Agarwal, Jawahar Lal; Garg, Sumit
Abstract : Objective: To compare emotional intelligence score with pre hypertension. To compare emotional intelligence score with heart rate variability (HRV). To compare pre hypertension with heart rate variability. Design and Method: 60 male adults (30 pre-hypertensives & 30 normotensive controls) age 25 to 50 years who were not a case of cardio vascular diseases, hypertension, diabetes or smoker were enrolled in the study. BP was measured by mercury sphygmomanometer taking all necessary precautions. Pre hypertension was defined as systolic BP from 121 to 139 mmHg or diastolic BP from 80 to 89 mmHg. Emotional intelligence (EI) was measured by Schutte Self Reported Emotional Intelligence Test and subjects were categorized into two groups: Group A: Low EI (Score < 111), Group B: High EI (Score > 111) ECG was recorded using standardized in-house-built Analogue ECG Amplifier, with Audacity 1.3.13 license free software in the supine position for 5 minutes after 10 minutes of rest. Every subject's raw data, filtered data and R-R interval in millisecond was opened in HRV Analysis free software V1.1license and the report sheet was saved. Results: Low EI was present in 20 pre-hypertensives and 3 normotensives. Mean EI score was significantly less in pre-hypertensives as compared to controls [109.5 vs 127.2 (p < 0.01)]. Low EI subjects had a significantly lower mean HFnu [46.12 vs 73.12 (p < 0.01)] and a significantly higher mean LF/HF ratio [1.27 vs 0.39 (p < 0.01)] showing lower parasympathetic and higher sympathetic activity in them. Pre-hypertensives had lower mean HFnu [54.73 vs 71.1 (p < 0.01)] and higher LF/HF ratio [1.03 vs 0.44 (p < 0.01)] showing lower parasympathetic and higher sympathetic activity in them. Conclusions: Low EI subjects are more prone to devlop pre-hypertension, had lower parasympathetic & higher sympathetic activity increasing the risk to develop hypertension in near future. Beside life style modification, improving EI is an important measure to prevent hypertension.